PENGARUH EFIKASI DIRI TERHADAP MOTIVASI BERORGANISASI MAHASISWA DI ORGANISASI KEMAHASISWAAN (OK) PTQ FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JAMBI - Arya Ramadhan; Muhammad Ferdiansyah; Rully Andi Yaksa (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Several campuses in Indonesia, even Jambi University, show that the level of student participation in student organizations is experiencing instability. Some students appear enthusiastic and active in carrying out organizational activities, but others show a low level of motivation or even withdraw from membership. Not a few student organizations experience stagnation due to the lack of member involvement, both in terms of implementing work programs and making strategic decisions. The aim of this research is to measure the influence of self-efficacy on student organizational motivation in the PTQ Student Organization (OK) Faculty of Teacher Training and Education, Jambi University with a total of 41 respondents. The research method used is quantitative, expost-facto approach, sampling using purposive sampling via questionnaires or questionnaires as a data collection tool. The research results show that there is a high influence of self-efficacy (X) on organizational motivation (Y), with a determination value of 0.630 or 63.0% in the High or Strong category.